Local Wisdom "Tabot and Batik Besurek" in Supporting City Branding Planning in Bengkulu Indonesia Province - Soni, Aprianto; Karman, Warsa Sugandi; YM, Hardiyanti; Yanasari, Wira (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2024)
Preserving Indonesian culture today by reviving the local wisdom of the people. Through local wisdom, Indonesian culture is believed to be able to build and solve problems related to society and culture. In local wisdom, there are various values that have been used by previous generations that can still be used by current and future generations, to solve problems, especially regarding the preservation of Indonesian culture. Methodologically, this study used a qualitative ethnographic method with a descriptive approach. The Tabot ceremony is a religious ceremony adapted into a cultural ethnic festival. The history of this ceremony originates from the tradition of the Shia sect which seeks to commemorate Husen's death in Padang Karbala, in 680. Apart from the Tabot, Bengkulu also has unique cultural heritage through Besurek batik cloth. very memorable. The meanings and values implied in it contain lessons that have an effect on human life in the city of Bengkulu and other areas. So that we can take values and apply them and adapt them in our daily lives. The concept of conserving Bengkulu local wisdom as a form of cultural identity is one of the aims of initiating the development of Bengkulu city branding. From the concept of city branding, Bengkulu will be a color in the national culture, giving identity to the Indonesian nation and can be used by all people. National culture gives a sense of pride in the Indonesian nation